Nanocarbon based composite electrodes and their application in microbial fuel cells. Issue 25 (14th June 2017) - Zhang, Yizhen; Liu, Lifen; Van der Bruggen, Bart; Yang, Fenglin
Abstract : Recent progress and applications of carbon nanotubes, graphene, g-C3 N4 and their composite electrodes in MFCs and MFC–MBRs are summarized. Abstract : Other than their use as new energy sources, microbial fuel cells (MFCs) are promising for wastewater treatment as they allow for significant energy savings and a high treatment efficiency if they are integrated with a MBR (membrane bioreactor), where the electricity can be in situ used over the cathode membrane, in spite of the insignificant power generation, the small current and low voltage output. The performance and cost of MFCs are largely influenced by the electrode materials. Nanocarbon materials with superior physical and chemical properties that conventional materials cannot match are crucial for the development of MFCs. In this review, recent research progress and applications of carbon nanotubes (CNTs), graphene, graphitic carbon nitride (g-C3 N4 ) and their composites as MFC anode/cathodes are highlighted, for insights into the characteristics, the modification/preparation methods and the performance of such MFCs. Different composite catalytic cathode membranes in integrated MFC–MBR systems are also reviewed. Integrating a MBR with a catalytic cathode membrane in MFCs improves the effluent quality and overcomes the deficiencies of MFC, while using the recovered bio-energy to offset the energy consumption for aeration and filtration.